Student teachers' self- and co-regulation of learning during teacher education. Issue 1 (2nd January 2016) - Saariaho, Emmi; Pyhältö, Kirsi; Toom, Auli; Pietarinen, Janne; Soini, Tiina
Abstract : Self-regulative learning skills are extremely important contributors in student teacher learning. Also, interest in co-regulation in learning as a facilitator for pupils' self-regulation skills and an ability to learn how to support peers' regulated learning has increased significantly during the past decade. Still, our understanding of student teachers' co- and self-regulative learning during their studies is shallow. This study aims to explore student teachers' self- and co-regulation of learning, including their elements and qualities embedded in various contexts of teacher education. In this study 19 primary school student teachers from a large research-based Finnish university were interviewed. The data were content analysed by applying an abductive strategy. The results showed that student teachers applied self-regulated learning more often than co-regulated learning, and that teaching practice provided a primary arena for regulative learning. Further investigation revealed that although self- and co-regulation had the same components, they differed in terms of the quality of regulation. Our findings suggest that co-regulated learning activities that involve peers and teacher educators reached a more profound and meaningful level when learning to become a teacher than learning activities involving self-regulated activities.